Student Perception of School Health Environment in SMA 2 State Unggulan Talang Ubi Regency Pali - Lestari, Ayu Agres; Utomo, Budi (Universitas Veteran Bangun Nusantara, 2020)
Lack of student awareness about the importance of environmental health causes school hygiene to become unhealthy. To find out students' perceptions about the health of the school environment in SMA Negeri 2 Unggulan Talang Ubi, Pali Regency.The method used in this research is descriptive qualitative method. The population in this study all class X students in SMA Negeri 2 Talang Ubi Pali Regency, amounting to 157 people. Determination of the sample using a random sampling technique where individuals selected randomly into a sample of 30 people from all grade X students in SMA Negeri 2 Unggulan Talang Ubi, Pali Regency. Data collection techniques used in this study were observation, documentation and questionnaires. The validity of the data used in this study is triangulation of data collection techniques by checking data to the same source with different techniques to get data from the same source and analyze data using the percentage formula. Based on the results of research that has been carried out to determine students' perceptions about school environmental health in SMA Negeri 2 Featured Talang Ubi in Pali Regency related to knowledge, understanding, attitudes and behavior of school environmental health by 75% have the perception that school environmental health is very important to maintain and creating environmental hygiene and health needs student self-awareness that starts with personal hygiene because if the school environment is not clean and healthy, disease transmission can occur through environmental media.